Thin multifunctional coatings for textiles based on the layer-by-layer application of polyaromatic hybrid nanoparticles - Babaeipour, Sahar; Nousiainen, Paula; Kimiaei, Erfan; Tienaho, Jenni; Kohlhuber, Nadine; Korpinen, Risto; Kaipanen, Kalle; Österberg, Monika (Royal Society of Chemistry (RSC), 2024)
The textile industry is striving to develop versatile coatings, combining antibacterial, water-repellent, and breathable properties, all while avoiding toxic components. However, the current solutions have unfavorable ecological impacts. Although the use of waxes has offered promise and is an eco-friendly option, there remains a challenge in achieving all the desired properties in a single solution. Here, we employed biobased nanoparticles, produced from natural fatty acid, tall oil fatty acid (TOFA) and lauric acid (La) esterified lignins and waxes, to create multifaceted textile coatings using a layer-by-layer deposition method. Our results reveal that even at nanoscale thickness, the developed coatings enhanced the water contact angle (WCA) of fabrics from 43° to ∼150° while maintaining good breathability (air permeability ranging between 23 and 31 mm/s. Moreover, the coated fabrics maintained excellent hydrophobicity even after two washing cycles. The surface morphology and roughness of the coatings characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM) showed a defect-free and integrated coating layer. Additionally, the polyaromatic molecules integrated into the coatings contributed to the textiles’ antibacterial properties against S. aureus (∼50% inhibition rate) and improved UV-shielding properties, demonstrating the potential for tailored functionality based on specific application requirements. Our systematic correlation of chemical structure and particle properties enabled a comprehensive understanding of their influence on the functionality and performance of coated fabrics. Furthermore, the layer-by-layer method utilizing biobased particles is a simple and efficient method to enhance the performance of cellulose-based materials. This positions the approach as a promising solution for widespread multifunctional textile applications, such as outdoor clothing.
Keywords: textiles; coatings; nanoparticles